Development of E-Learning Teaching Materials Based on Guided Inquiry Learning Models and Camtasia Applications to Support Post-COVID-19 Online Learning for Chemistry Teachers in SMA / MA - Mawardi Mawardi; Zonalia Fitriza; Okta Suryani (Fakultas MIPA Universitas Negeri Padang, 2021)
The increasing number of positive cases of COVID-19 in Indonesia has prompted the Ministry of Education and Culture (Kemendikbud) to recommend online learning as an effort to reduce the spread of the virus. The use of new online learning technology is dominated by SMA / MA in big cities because of the financial capacity and availability of a digital learning system that is better than SMA / MA in remote areas. The problem currently faced is the unavailability of teaching materials oriented to the online learning process (e-learning) in accordance with the demands of the 2013 Curriculum and the ability of most educators to prepare teaching materials for independent online learning still needs to be improved. Therefore, community service training in the development / manufacture of teaching materials that is oriented to the guided inquiry learning model and applies three types of representation to express chemical ideas, so that the chemistry learning process produces three learning levels, namely symbolic representation, macroscopic and sub-microscopic, or molecular. Have been trained to use Camtasia aplication.